2017 annual report on intra-EU labour mobility. Final report January 2018 - Fries-Tersch, Elena; Tugran, Tugce; Rossi, Ludovica; Bradley, Harriet (Luxembourg, 2018)
"In 2016 some 11.8 million EU citizens of working age were living in an EU country other than their own. This report presents an overview of mobility and its characteristics within the EU and the EFTA countries. In addition, the report focuses this year on the gender dimension of mobility, language and other barriers to cross-border mobility in neighbouring regions; and at the mobility of health professionals."